2006
DOI: 10.1108/09513550610650400
|View full text |Cite
|
Sign up to set email alerts
|

Unit cost behaviour in public sector outsourcing

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…IT outsourcing in the public sector conforms to the practices of the private sector (Kulmala et al 2006). This conformation leads the public sector IT managers to refer the findings and the implications of private sector research when IS/IT outsourcing projects are planned.…”
Section: Introductionmentioning
confidence: 94%
“…IT outsourcing in the public sector conforms to the practices of the private sector (Kulmala et al 2006). This conformation leads the public sector IT managers to refer the findings and the implications of private sector research when IS/IT outsourcing projects are planned.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, it is hard to find "good guidebooks" dealing with public sector IT outsourcing. Moreover, it has to be noted that while there are many previous studies regarding IT outsourcing in the public sector, there are very few reported studies concentrating on overall service production [14].…”
Section: It Outsourcing In the Public Sectormentioning
confidence: 99%
“…That is, public sector IT managers are adopting outsourcing as a management strategy to achieve flexible staffing, greater technological proficiency, and lower costs [11][12][13]. In this sense, IT outsourcing in the public sector also includes similar practices of private sector planning, funding, implementation and temporary assignments given by the public sector [14]. This is the reason that public sector IT managers have frequently referred to findings and implications from MIS research when they plan public sector outsourcing projects.…”
Section: It Outsourcing In the Public Sectormentioning
confidence: 99%
“…The basic idea of the quasimarket is to combine the advantages of public authorities to compensate for market failure with mechanisms that protect against government failure. Ideally, the result improves efficiency (Kulmala et al,2006). Boardman and Vining (1992) raised the question about the significance of both competition and ownership in a public company.…”
Section: Empirical Reviewmentioning
confidence: 99%